2016
DOI: 10.1007/s00701-016-2725-4
|View full text |Cite
|
Sign up to set email alerts
|

One-pass deep brain stimulation of dentato-rubro-thalamic tract and subthalamic nucleus for tremor-dominant or equivalent type Parkinson’s disease

Abstract: BackgroundRefractory tremor in tremor-dominant (TD) or equivalent-type (EQT) idiopathic Parkinson’s syndrome (IPS) poses the challenge of choosing the best target region to for deep brain stimulation (DBS). While the subthalamic nucleus is typically chosen in younger patients as the target for dopamine-responsive motor symptoms, it is more complicated if tremor does not (fully) respond under trial conditions. In this report, we present the first results from simultaneous bilateral DBS of the DRT (dentato-rubro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 28 publications
1
51
0
Order By: Relevance
“…Advanced imaging with individualized visualization of target structures is increasingly being used for personalized and direct stimulation planning. [8][9][10][11] However, imaging-assisted directional stimulation requires detailed knowledge of the exact orientation of the electrode array with respect to its functional environment. The exact orientation of the segmented leads has to be determined by postoperative imaging because the degree of rotation varies during implantation and fixation of the electrode.…”
Section: Eep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…Advanced imaging with individualized visualization of target structures is increasingly being used for personalized and direct stimulation planning. [8][9][10][11] However, imaging-assisted directional stimulation requires detailed knowledge of the exact orientation of the electrode array with respect to its functional environment. The exact orientation of the segmented leads has to be determined by postoperative imaging because the degree of rotation varies during implantation and fixation of the electrode.…”
Section: Eep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…We recently showed, in a prospective study, that direct targeting of the DRTt using deterministic tractography provided excellent tremor control, which had before been described in case reports . However, it is unclear whether targeting an electrode in very close proximity to a depicted tract yields superior results to indirect targeting of the Vim thalamus.…”
mentioning
confidence: 92%
“…The use of diffusion tensor tractographic methods has shown that these targets likely lie along part of the same cerebello‐thalamic‐cortical network, or the dentato‐rubro‐thalamic tract (DRTt), where the more proximal targets intercept tract fibers that are more concentrated before fanning out in the thalamus . Some experts contend that modulation of the DRTt fibers may, in fact, be responsible for tremor suppression applied at any of these targets …”
mentioning
confidence: 99%
“…It has been reported18192021222324252627282930313233343536 that implanting leads to multiple targets is of important practical value. In terms of treating diseases, quadruple-targeted DBS might lead to better treatment results compared to dual-targeted DBS18192021222324.…”
mentioning
confidence: 99%
“…Only limited research343536 demonstrated that a single lead can be delivered to two targets in sequence through a “straight lead pathway”. This “straight lead pathway” method is suitable for only a few combinations of targets, such as internal globus pallidus (GPi) + external globus pallidus (GPe)35 or internal capsule + accumbens nucleus36, and is not applicable when the distance between the two targets is far, or the extension of the line that connects the two targets is not a suitable pathway for lead implantation.…”
mentioning
confidence: 99%